Impact of the Centers for Medicare and Medicaid Services Sepsis Core Measure on Antibiotic Use. (22nd August 2020) - Pakyz, Amy L; Orndahl, Christine M; Johns, Alicia; Harless, David W; Morgan, Daniel J; Bearman, Gonzalo; Hohmann, Samuel F; Stevens, Michael P
Abstract: Background: The Centers for Medicare and Medicaid Services (CMS) implemented a core measure sepsis (SEP-1) bundle in 2015. One element was initiation of broad-spectrum antibiotics within 3 hours of diagnosis. The policy has the potential to increase antibiotic use and Clostridioides difficile infection (CDI). We evaluated the impact of SEP-1 implementation on broad-spectrum antibiotic use and CDI occurrence rates. Methods: Monthly adult antibiotic data for 4 antibiotic categories (surgical prophylaxis, broad-spectrum for community-acquired infections, broad-spectrum for hospital-onset/multidrug-resistant [MDR] organisms, and anti–methicillin-resistant Staphylococcus aureus [MRSA]) from 111 hospitals participating in the Clinical Data Base Resource Manager were evaluated in periods before (October 2014–September 2015) and after (October 2015–June 2017) policy implementation. Interrupted time series analyses, using negative binomial regression, evaluated changes in antibiotic category use and CDI rates. Results: At the hospital level, there was an immediate increase in the level of broad-spectrum agents for hospital-onset/MDR organisms (+2.3%, P = .0375) as well as a long-term increase in trend (+0.4% per month, P = .0273). There was also an immediate increase in level of overall antibiotic use (+1.4%, P = .0293). CDI rates unexpectedly decreased at the time of SEP-1 implementation. When analyses were limited to patients with sepsis, there was a significant level increase in use of all antibiotic categories at the time of SEP-1 implementation. Conclusions: SEP-1 implementation was associated with immediate and long-term increases in broad-spectrum hospital-onset/MDR organism antibiotics. Antimicrobial stewardship programs should evaluate sepsis treatment for opportunities to de-escalate broad therapy as indicated. Abstract : After implementation of the sepsis quality measure in 2015, there was an immediate and long-term increase in use of broad-spectrum antibiotics for hospital-onset/multidrug-resistant bacteria, as well as an immediate increase in overall antibiotic use.